Biosafety considerations for attenuated measles virus vectors used in virotherapy and vaccination. Issue 5 (3rd May 2016) - Baldo, Aline; Galanis, Evanthia; Tangy, Frédéric; Herman, Philippe
ABSTRACT: Attenuated measles virus (MV) is one of the most effective and safe vaccines available, making it attractive candidate vector to prevent infectious diseases. Attenuated MV have acquired the ability to use the complement regulator CD46 as a major receptor to mediate virus entry and intercellular fusion. Therefore, attenuated MV strains preferentially infect and destroy a wide variety of cancer cells making them also attractive oncolytic vectors. The use of recombinant MV vector has to comply with various regulatory requirements, particularly relating to the assessment of potential risks for human health and the environment. The present article highlights the main characteristics of MV and recombinant MV vectors used for vaccination and virotherapy and discusses these features from a biosafety point of view.